Capnography monitoring during dental conscious sedation. (13th September 2016) - Brady, P.; Gallagher, C.; McCarthy, C.; O'Halloran, K.; McCreary, C.; Ioham, G.
Abstract: Aim: This article aims to provide some useful information on implementing capnography monitoring and interpretation in an oral surgery setting. Materials and Methods: Information gleaned from experience in the use of microstream capnography for patients undergoing conscious sedation is presented. Results: Waveform trend rather than quantitative measurement of end tidal carbon dioxide is emphasised for monitoring spontaneously breathing patients. Conclusion: The information presented provides dentistry‐specific information on capnography monitoring.